Clinical significance of microbiota changes under the influence of psychotropic drugs. An updated narrative review - Misera, Agata; Łoniewski, Igor; Palma, Joanna; Kulaszyńska, Monika; Czarnecka, Wiktoria; Kaczmarczyk, Mariusz; Liśkiewicz, Paweł; Samochowiec, Jerzy; Skonieczna-Żydecka, Karolina (Frontiers in Microbiology, 2023)
Relationship between drugs and microbiota is bilateral. Proper composition thus function of microbiota is a key to some medications used in modern medicine. However, there is also the other side of the coin. Pharmacotherapeutic agents can modify the microbiota significantly, which consequently affects its function. A recently published study showed that nearly 25% of drugs administered to humans have antimicrobial effects. Multiple antidepressants are antimicrobials,. and antibiotics with proven antidepressant effects do exist. On the other hand, antibiotics (e.g. isoniaside, monocycline) confer mental phenotype changes, and adverse effects caused by some antibiotics include neurological and psychological symptoms which further supports the hypothesis that intestinal microbiota may affect the function of the central nervous system. Here we gathered comprehensively data on drugs used in psychiatry regarding their antimicrobial properties. We believe our data has strong implications for the treatment of psychiatric entities. Nevertheless the study of ours highlights the need for more well-designed trials aimed at analysis of gut microbiota function.